2020
DOI: 10.1111/cas.14260
|View full text |Cite
|
Sign up to set email alerts
|

Phase I study of vorinostat with gefitinib in BIM deletion polymorphism/epidermal growth factor receptor mutation double‐positive lung cancer

Abstract: Patients with epidermal growth factor receptor (EGFR)-mutated non-small cell lung cancer (NSCLC) harboring BIM deletion polymorphism (BIM deletion) have poor responses to EGFR TKI. Mechanistically, the BIM deletion induces preferential splicing of the non-functional exon 3-containing isoform over the functional exon 4-containing isoform, impairing TKI-induced, BIM-dependent apoptosis. Histone deacetylase inhibitor, vorinostat, resensitizes BIM deletion-containing NSCLC cells to EGFR-TKI.In the present study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 34 publications
(49 reference statements)
0
28
0
Order By: Relevance
“…A preclinical study by Nakagawa et al found that combining EGFR-TKIs with histone deacetylase (HDAC) inhibition could circumvent the resistance induced by BIM-del [14]. Furthermore, a recent phase I study of patients with BIM-del and EGFR-mutant double-positive lung cancer who were treated with an HDAC inhibitor (vorinostat) and gefitinib in combination obtained satisfying results with regard to safety and ascertained 400 mg of vorinostat as the recommended dose for a phase II study [15]. Additionally, EGFR-TKIs plus chemotherapy also showed a significant clinical benefit compared to EGFR-TKI monotherapy in advanced NSCLC patients with EGFR mutation and BIM-del [10].…”
Section: Discussionmentioning
confidence: 99%
“…A preclinical study by Nakagawa et al found that combining EGFR-TKIs with histone deacetylase (HDAC) inhibition could circumvent the resistance induced by BIM-del [14]. Furthermore, a recent phase I study of patients with BIM-del and EGFR-mutant double-positive lung cancer who were treated with an HDAC inhibitor (vorinostat) and gefitinib in combination obtained satisfying results with regard to safety and ascertained 400 mg of vorinostat as the recommended dose for a phase II study [15]. Additionally, EGFR-TKIs plus chemotherapy also showed a significant clinical benefit compared to EGFR-TKI monotherapy in advanced NSCLC patients with EGFR mutation and BIM-del [10].…”
Section: Discussionmentioning
confidence: 99%
“…Vorinostat was insufficient to reverse EGFR-TKI acquired resistance in EGFR mutant condition [ 364 ]. Similarly, vorinostat failed to improve PFS in combination with gefitinib in other clinical trials including patients with EGFR-mutant NSCLC [ 365 , 366 ]. ICI and particularly pembrolizumab combined with vorinostat (400 mg/day) was explored in a phase 1 study, including 33 patients with advanced NSCLC.…”
Section: Hypoxia-related Treatments and Research Developmentmentioning
confidence: 99%
“…EGFR-TKI combination therapy with histone deacetylase (HDAC) inhibitors may be one approach to overcome the inferior outcomes conferred by the BIM deletion. A recent phase I study with 12 patients treated with the combination of gefitinib and vorinostat (a small-molecule HDAC inhibitor) revealed a DCR of 83.3% (10/12) at six weeks, with a median PFS of 5.2 months (95% CI, 1.4–15.7) ( 43 ). In addition, retrospective analysis revealed that EGFR-TKIs plus chemotherapy conferred a significantly higher ORR (65.5 vs. 38.9%, p = 0.046), prolonged PFS (7.2 vs. 4.7 months; p = 0.008) and a longer OS (18.5 vs. 14.2 months; p = 0.107) compared to TKIs alone in advanced NSCLC patients with EGFR mutations and BIM deletion polymorphism ( 176 ).…”
Section: Other Biomarkersmentioning
confidence: 99%